Early evaluation of survival of the transplanted ovaries through ultrasound molecular imaging via targeted nanobubbles. (2nd September 2020) - Zhang, Shan; Di, Na; Tayier, Baihetiya; Guan, Lina; Wang, Guodong; Lu, Hanbing; Yan, Fei; Mu, Yuming
Abstract : Schematic of AMH-targeted nanobubbles (NBAMH ) and their targeting ability to rat ovarian granulosa cells expressing AMH. Abstract : Ovarian survival after transplantation is key to determining the success and efficacy of ovarian tissue cryopreservation and transplantation (OTCP). However, non-invasive monitoring of ovarian survival in the early stages of ovarian transplantation remains a great challenge. Anti-Müllerian hormone (AMH) is a survival factor that can promote the growth of follicles and has been recognized as an ovarian tissue-specific marker. In this study, we developed AMH-targeted nanobubbles (NBAMH ) by integrating an AMH antibody onto the surface of NBs. The resulting NBAMH exhibited a high affinity for ovarian granulosa cells in vitro and a significantly enhanced ultrasound signal in transplanted ovaries relative to the non-targeted NBs. Notably, the difference in enhanced ultrasonic signals became more significant with the increase in time after transplantation from 3 to 10 days, indicating a gradually enhanced AMH expression along with the increase in transplant time. These results were further confirmed by immunohistochemical staining and western immunoblotting analyses. In conclusion, our study offers a promising non-invasive tool to monitor ovarian survival in the early stages following transplantation.